Acculturation Factors Related to Obesity of Latino American Men Nationwide. Issue 5 (September 2018) - Ai, Amy L.; Appel, Hoa B.; Lee, Jungup
Obesity is a public health epidemic, particularly among underrepresented populations. With a large proportion of immigrants, Latino Americans comprise the largest minority population in the United States. This study examined the association of acculturation factors with obesity among Latino American men ( n = 1, 127) using the National Latino and Asian American Study. The result identified two acculturation-related factors (being U.S.-born and living in the United States for the longest period/5-10 years) as positive correlates. In contrast, a different study on obesity in Latino American women demonstrated discrimination, but not the above factors, as significant correlates. The men's pattern suggests that the Hispanic/Latino paradox might have greater implications for men with respect to weight issues. Furthermore, Mexican American and Other Latino American men presented a greater likelihood of being obese than Cuban and Puerto Rican men. The findings, if replicated in prospective research, suggest the need for gender- and ethnic-specific intervention for obesity in Latino American men, particularly for the largest subgroup, Mexican Americans.